Level of awareness among students of Tanauan school of craftsmanship and home industries regarding the Tanauan community e-center. - Cornejo, Ma. Flodelyn (Tacloban City Ma. Flodelyn Cornejo [and] Paul Nigel Dalida Custodio, 2010)
This is a descriptive correlational study on the level of awareness among students of Tanauan School of Craftsmanship and Home Industries regarding the Tanauan Community e-Center. The objectives of the study include: to determine the socio-economic and demographic characteristics of the respondents; to know the level of awareness among the students regarding the Tanauan Community e-Center; to identify the relationship of the socio-economic variables and level of awareness; and to find out the implications of level of awareness on the effectiveness and sustainability of the Tanauan Community e-Center.
This research was conducted in Tanauan, Leyte. The respondents of this study are students from Tanauan School of Craftsmanship and Home Industries determined using stratified random sampling and simple random sampling. This study used self-administered questionnaire and schedule interview. The results from the questionnaires were tabulated for statistical treatment. Frequency distribution, mean and standard deviation, point biserial, eta, Pearson's Moment Product and p-value are statistical tools used. Responses of key informant interview were summarized, categorized and described.
Results showed that the respondents are quite well informed on the establishment of the Tanauan Community e-Center. Socio-economic and demographic variables and level of awareness among students do not have significant relationship. The researchers found most respondents aware of the Tanauan Community e-Center where positive and negative comments have been elicited. A number of respondents were as well not aware on the establishment of the said community e-Center which further suggests an initiative of the local government unit of Tanauan to patronize the said community e-Center. The Tanauan Community e-Center is recognized as one of the students' venue for research. Financial constraints are seen barrier of the students to avail of the services offered by the Tanauan Community e-Center which further suggest adjustments in the policies of the community e-Center.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science